2016
DOI: 10.1155/2016/5127682
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Molecule Clustering by Hydrogen Bond in Hydrous Ethanol on Laminar Burning Velocity

Abstract: The role of hydrogen bond molecule clustering in laminar burning velocities was observed. The water in hydrous ethanol can change the interaction between water-ethanol molecules. A certain amount of water can become oxygenated which increases the burning velocity. The hydrogen bond interaction pattern of ethanol and water molecules was modeled. Based on the molecular model, azeotropic behavior emerges from ethanol-water hydrogen bond, which is at a 95.1%v composition. The interaction with water molecule causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…(b) Anhydrous ethanol is added with n-heptane. [12] showed that the composition of azeotropic hydrous ethanol occurs at a 95.1% v composition with the molecular structure as in Figure 9(a). The maximum burning velocity of hydrous ethanol occurs at a 95.5% v composition with the molecular structure as in Figure 9(b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) Anhydrous ethanol is added with n-heptane. [12] showed that the composition of azeotropic hydrous ethanol occurs at a 95.1% v composition with the molecular structure as in Figure 9(a). The maximum burning velocity of hydrous ethanol occurs at a 95.5% v composition with the molecular structure as in Figure 9(b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the objective of this study is to acquire new data about laminar burning velocity of the mixtures of anhydrous ethanol (99.7% v) and hydrous ethanol (95.5% v) with n-heptane in varied composition at lean ( = 0.9), stoichiometric ( = 1), rich ( = 1.1), and very rich mixture ( = 1.2). It is motivated by the characteristics of hydrous ethanol fuel which is better than anhydrous ethanol at the stoichiometric and rich mixture [12]. The mixture of ethanol/nheptane can combine the renewable fuel with fossil fuel.…”
Section: Journal Of Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors affect the combustion process, among which are fatty acids, polarity and the potential of electricity from fatty acids. Gas-fired research has also been examined by [8,9], revealing speed in the combustion chamber. The results showed that the hydro ethanol combustion rate was higher than anhydrous ethanol and N-Heptane in the stoichiometric mixture.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%